Ignition delay of diisobutylene-containing multicomponent gasoline surrogates: Shock tube measurements and modeling study. (1st January 2019) - Li, Hua; Qiu, Yue; Wu, Zhiyong; Wang, Sixu; Lu, Xingcai; Huang, Zhen
Highlights: Three multicomponent gasoline surrogates containing diisobutylene were constructed. The ignition delay of the surrogates was measured under different conditions. A chemical kinetic model for gasoline surrogates was generated and validated. Flux and sensitivity analyses were performed to study the effects of condition parameters. Abstract: Two quaternary and one quinary surrogates containing diisobutylene are constructed according to the characteristics of gasoline with a research octane number of 95. The ignition delay measurements for all three surrogates are performed in a high-pressure shock tube at pressures of 10/15/20 bar, equivalence ratios of 0.5/1.0/2.0, in the temperature range of 950–1300 K with exhaust gas recirculation loadings ranging from 0% to 60%. A chemical kinetic model composed of 563 species and 2915 reactions is generated to describe the ignition features of gasoline surrogates. It is validated by numerous experimental data of ignition delay for isooctane, n-heptane, toluene, diisobutylene, cyclohexane and their mixtures with the comparison of other proposed chemical mechanisms in the literature. Satisfactory agreement is obtained between the measurements and simulated data for all three surrogates, which illustrates the negative correlation of temperature, pressure and equivalence ratio with ignition delay, and the inhibitive effects of EGR on the system reactivity. Moreover, the sensitivity, reaction flux and rate of production analyses, and the history of reactive radicals are explored with different temperatures, pressures, equivalence ratios and EGR rates. The results reveal the remarkable dependence of ignition delay on the temperature than other parameters and indicate the predominant dilution and thermal effects of CO2 on the ignition of the quinary gasoline surrogate.